A unique system that can sensitively assess the risk of chemical leukoderma by using murine tail skin. (November 2019) - Iida, Machiko; Tazaki, Akira; Deng, Yuqi; Chen, Wei; Yajima, Ichiro; Kondo-Ida, Lisa; Hashimoto, Kazunori; Ohgami, Nobutaka; Kato, Masashi
Abstract: Chemical leukoderma is a patchy hypopigmentation in the skin. Phenol derivatives such as raspberry ketone have been reported to cause the development of occupationally induced leukoderma. Recently, 2% (w/w) rhododenol, a reduced form of raspberry ketone used in a skin-lightning agent, also caused the development of leukoderma in >16, 000 users, about 2% of all users, in Asian countries including Japan. However, a method for assessing the risk of leukoderma caused by 2% rhododenol has not been established despite the fact that the development of leukoderma caused by 30% rhododenol was previously shown in animal experiments. Establishment of a novel technique for risk assessment of leukoderma in humans caused by external treatment with chemicals is needed to prevent a possible future chemical disaster. This study demonstrated that external treatment with 2% rhododenol and the same concentration of raspberry ketone caused the development of leukoderma in murine tail skin without exception with significant decreases in the amount of melanin and number of melanocytes in the epidermis. Thus, a novel in vivo technique that can assess the risk of leukoderma caused by 2% rhododenol was developed. The unique technique using tail skin has the potential to prevent chemical leukoderma in the future. Graphical abstract: Image 1 Highlights: 2% rhododenol caused leukoderma in >16, 000 users in Asian countries. Establishment of a technique for risk assessment of leukoderma is an urgent task. A system to assess the risk of leukoderma caused by 2% rhododenol was developed. 2% rhododenol caused decreases in the levels of melanin and melanocytes. Our risk assessment technique has the potential to prevent chemical leukoderma.